Calcitonin gene-related peptide: an update on the biology - Recober, Ana (2009)
PURPOSE OF REVIEW: This review includes the most relevant and recent studies on the biology of calcitonin gene-related peptide (CGRP) as it pertains to primary headaches and particularly to migraine. Especial attention was given to those published within the last year. RECENT FINDINGS: The development of CGRP receptor antagonists is discussed in detail, as well as recent advances in our understanding of CGRP actions in migraine. Finally, other important functions of CGRP outside of the nervous system are briefly discussed. SUMMARY: The advent of CGRP receptor antagonists as a novel therapy for migraine attacks may represent a new era in the acute management of migraine. More than a simple addition to the currently available treatments, this group of drugs may become an outstanding option for patients with cardiovascular disease, given the lack of associated vasoconstriction. Furthermore, nonpeptide CGRP receptor antagonists, CGRP antibodies and CGRP-binding RNA-Spiegelmer are valuable research tools that will further advance our understanding of migraine pathophysiology.